2020
DOI: 10.3389/fneur.2020.00855
|View full text |Cite
|
Sign up to set email alerts
|

The Suppressive Effect of the Motor System on the Sensory System in Patients With Tourette Syndrome

Abstract: Objective: Tourette syndrome (TS) is a complicated sensorimotor disorder. Some patients with TS relieve their involuntary premonitory urges via tics. However, the effect of the motor system on the sensory system has not yet been elucidated. The purpose of the present study was to investigate changes in the excitability of the sensory cortex following repetitive transcranial magnetic stimulation (rTMS) of the motor cortex in patients with TS. Methods: Twenty-nine patients with TS and 20 healthy, age-matched con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Sun and colleagues explored the suppressive effect of the motor system on the sensory system in TS patients ( Sun et al . 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun and colleagues explored the suppressive effect of the motor system on the sensory system in TS patients ( Sun et al . 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sun and colleagues explored the suppressive effect of the motor system on the sensory system in TS patients (Sun et al 2020). They used a sham-controlled repetitive Transcranial Magnetic Stimulation (rTMS) protocol (1Hz, 90% of the resting motor threshold) and recorded the somatosensory evoked potentials before and 15 minutes after rTMS.…”
Section: Electrophysiologymentioning
confidence: 99%
“…The lead author (KD) screened the titles and abstracts of the remaining articles using the eligibility criteria, which resulted in 24 articles for retrieval. Of these, a further 6 were excluded; 5 as they did not involve pre/post measures of tic change (Marsili et al 2017 ; Sun et al 2020 ; Suppa et al 2011 ; Suppa et al 2014 ; Wu and Gilbert 2012 ) and 1 additional case study as the participant withdrew early (Salatino et al 2014 ).…”
Section: Results Of Systematic Reviewmentioning
confidence: 99%
“…A previous meta-analysis confirmed that low frequency was more effective in the treatment of TD [33], which is consistent with the results of our review. The rTMS targets were mainly the SMA, but other targets included the parietal cortex, motor area or premotor area [35,45,[54][55][56]. The review showed that the ratio of low frequency rTMS of the SMA was often used in many studies because the SMA plays an important role in the connection of the cortical, basal ganglia, and thalamic regions, which are related to the motor circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in half of the 12 studies received 1200 stimuli per day [35,36,42,52,53,55]. Participants in only one study underwent low frequency 200 ms stimulation [56]. The only common evaluation of all studies was based on the Yale Global Tic Severity Scale (YGTSS).…”
Section: Rtms For Tdmentioning
confidence: 99%